Synergistic Antitumor Effect of α-pinene and β-pinene with Paclitaxel against Non-small-cell Lung Carcinoma (NSCLC) - Zhang, Z.; Guo, S.; Liu, X.; Gao, X. (Drug Research, 2015)
The objective of the present research work was to evaluate the synergistic interactions between Paclitaxel (PAC) with α-pinene and β-pinene using isobolographic method against non-small-cell lung cancer cells (NSCLC). This type of interaction between an established drug and a new compound is expected to enhance the efficacy of paclitaxel in combination as compared in isolation. Further, cell cycle analysis was carried out using flow cytometric analysis. Phase contrast microscopy was used to assess the effect of paclitaxel, α-pinene and β-pinene alone and in combination with each other in order to evaluate the effect of combination on cell apoptosis. Further, mitochondrial membrane potential was monitored in non-small-cell lung cancer cells (NSCLC) when treated with paclitaxel, α-pinene and β-pinene alone and in combination. The results revealed that the combination of PAC with α-pinene or with β-pinene showed a plotted curve below the straight line, generating a substantial synergistic effect. The effects of the following combinations were examined utilizing isobolograms: PAC and α-pinene and PAC and β-pinene. The combination of PAC and α-pinene as well as of PAC and β-pinene actually generated a synergistic effect. We also examined the effects of these compounds on the cell cycle distributions of A549 cells by flow cytometric analysis. The percentage of sub-G0/G1-phase cells was decreased on the addition of α-pinene to PAC, while the population of G0/G1 cells was increased. The morphological changes characteristic of apoptosis like chromatin condensation and fragmentation of the nucleus were seen in PAC+α-pinene and PAC+β-pinene treated NSCLC cells.
Keywords: paclitaxel; non-small-cell lung cancer; synergy; α-pinene; anticancer activity